High Expression of Interleukin-3 Receptor Alpha Chain (CD123) Predicts Favorable Outcome in Pediatric B-Cell Acute Lymphoblastic Leukemia Lacking Prognosis-Defining Genomic Aberrations - Li, Zhiheng; Chu, Xinran; Gao, Li; Ling, Jing; Xiao, Peifang; Lu, Jun; Wang, Yi; He, Hailong; Li, Jianqin; Hu, Yixin; Li, Jie; Pan, Jian; et al. (Frontiers in Oncology, 2021)
Background Aberrant expression of CD123 (IL-3Rα) was observed in various hematological malignancies including acute lymphoblastic leukemia (ALL), which is the most common malignancy in childhood. Although widely used for minimal residual disease (MRD) monitoring, the prognostic value of CD123 has not been fully characterized in pediatric B-ALL. This retrospective study aims to evaluate the association between the CD123 expression of leukemic blasts and the outcomes of the pediatric B-ALL patients. Methods A total of 976 pediatric B-ALL, including 328 treated with CCLG-ALL-2008 protocol and 648 treated with CCCG-ALL-2015 protocol, were recruited in this retrospective study. CD123 expression was evaluated by flow cytometry. Patients with >50%, 20-50% or <20% of CD123 expressing blasts were grouped into CD123high, CD123low, and CD123neg, respectively. The correlation between CD123 expression and the patients' clinical characteristics, overall survival (OS), event-free survival (EFS), and relapse-free survival (RFS) were studied statistically. Results: Of 976 pediatric B-ALL, 53.4% from the CCLG-ALL-2008 cohort and 49.2% from the CCCG-ALL-2015 cohort were CD123high. In the CCLG-ALL-2008 cohort, CD123high was significantly associated with chromosome hyperdiploidy (p<0.0001), risk stratification (p=0.004), and high survival rate (p=0.005). By comparing clinical outcomes, patients with CD123high displayed favorable prognosis, with a significantly better OS (p=0.005), EFS (p=0.017), and RFS (p=0.045), as compared to patients with CD123low and CD123neg. The prognostic value of CD123 expression was subsequently confirmed in the CCCG-ALL-2015 cohort. Univariate and multivariate cox regression model analysis showed that high CD123 expression was independently associated with favorable EFS (OR: 0.528; 95% CI: 0.327 to 0.853; p=0.009) in this cohort. In patients without prognosis-defining genetic abnormalities, high CD123 expression strongly indicated superior survival rates and was identified as an independent prognosis factor for EFS and RFS in both cohorts. Conclusions A group of B-ALL lacks prognosis-defining genomic aberrations, which proposes a challenge in risk stratification. Our findings revealed that high CD123 expression of leukemic blasts was associated with favorable clinical outcomes in pediatric B-ALL and CD123 could serve as a promising prognosis predictor, especially in patients without prognosis-defining genetic aberrations.